Resolution of venous thrombosis using a novel oral small-molecule inhibitor of P-selectin (PSI-697) without anticoagulation - Myers, Daniel D., Jr.; Wrobleski, Shirley K.; Longo, Chris; Bedard, Patricia W.; Kaila, Neelu; Shaw, George D.; Londy, Frank J.; Rohrer, Suzan E.; Fex, Beverly A.; Zajkowski, Paul J.; Meier, Thomas R.; Hawley, Angela E.; Farris, Diana M.; Ballard, Nicole E.; Henke, Peter K.; Schaub, Robert G.; Wakefield, Thomas W. (Thrombosis and Haemostasis, 2007)
P-selectin inhibition has been shown to decrease thrombogenesis in multiple animal species. In this study, we show that a novel oral small-molecule inhibitor of P-selectin, PSI-697, promotes thrombus resolution and decreases inflammation in a baboon model of venous thrombosis. Experimental groups consisted of the following: 1) primates receiving a single oral dose of PSI-697 (30 mg/kg) daily starting three days pre-iliac vein balloon occlusion, and continued for six days; 2) primates receiving a single treatment dose of a low-molecular-weight-heparin (LMVVH) (1.5 mg/kg) daily starting one day pre-iliac balloon occlusion, and continued for six days; and 3) primates receiving a single oral dose of a vehicle control daily starting three days pre-iliac vein balloon occlusion, and continued for six days. Animals receiving PSI-697, although thrombosed after balloon deflation, demonstrated greater than 80% vein lumen opening over time, with no opening (0%) for vehicle control (p<0.01). LMVVH opening evident after balloon deflation slightly deteriorated overtime compared to PSI-697. PSI-697 therapy also significantly decreased vein wall inflammation determined by magnetic resonance venography (MRV). Importantly, this beneficial opening occurred without measured anticoagulation. Animals receiving PSI-697 demonstrated significantly increased plasma D-dimer levels versus LMVVH and control animals six hours post thrombus induction (p<0.01). This study is the first to demonstrate the effectiveness of oral P-selectin inhibition to modify venous thrombogenesis, increase vein lumen opening, and decrease inflammation in a large animal model.
Keywords: Deep venous thrombosis; thrombus resolution; small-molecule inhibitor of p-selectin; inflammation; animal models